A single beam smart antenna for wireless communication in a highly reflective and narrow environment - Pirapaharan, K.; Herman, Kunsei; Senthilkumar, K.S.; Hoole, P.R.P; Hoole, S.R.H. (IEEE, 2017)
Multipath reflections are prevalent in underground mine wireless communication systems and are less constructive when an omnidirectional antenna is used. This phenomenon can be significantly controlled by eliminating the source of all multipaths with a single beam. The single beam must be rotatable towards the desired user to be of any use. The single directed beam will avoid generating multipath reflections and efficiently consume the valuable stored energy. In this paper we present an analysis of an array antenna using dipoles that forms a single beam without the need for reflectors or any complex arrangement of the array elements. It can be shown that dipole elements placed in a straight line are not effective in minimizing energy consumption and a minimum of three elements are sufficient for forming a single directed beam that is electronically rotatable to all directions. We have compared three, four and six elements for the accuracy. It is also shown that the elements of the array antenna should b placed on the circumference of a circle to avoid re-computation of weights to rotate the beam on to any desired direction, thus significantly reducing the computational burden of the single beam, steerable smart antenna.